The role of the household and community in determining child health - Subha Mani (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2007)
Nutritional status at a young age is positively associated with an individual's total human capital accumulated. Higher levels of human capital are in turn strongly correlated with an individual's economic and social well-being. Health is one such dimension of human capital and improvements in children's nutritional status improve an individual's overall lifetime well-being. This paper examines the various child level, household level, and community level characteristics that determine health status among children. The paper uses data from the three waves of the Indonesian Family Life Survey to assess the gender-specific determinants of child health outcomes. I do not find any evidence for gender-differential impact of the household and community characteristics in determining child health. I find that household characteristics like parental height have a strong positive effect on determining child health. There is some evidence supporting the positive association between household income and child health. Among the community infrastructure variables – measure of prevalence of electricity in the community and dummy for presence of paved road in the community are both positively associated with child health. The results obtained here are robust to a number of econometric concerns like measurement error in household income variable, correlation between community time-invariant unobservables and household specific unobservables, correlation between community time-invariant unobservables and community resource availability variables. Community level fixed-effects along with IV techniques used in this paper address the aforementioned methodological concerns.
Keywords: D10; I10; O10; O12; 330; child health; well-being; nutrition; Indonesia